IMPLEMENTASI METODE WEIGHT PRODUCT UNTUK PENILAIAN KINERJA KARYAWAN DI PT. PERTAMINA GAS - Wardana, Bendra (Department of Information System Muhammadiyah University of Riau, 2024)
In an office routine, recording employee data is an unavoidable necessity. This data collection has the main purpose of evaluating employee performance, thereby enabling appropriate rewards to be given as a means of increasing their motivation in carrying out their duties. To solve the problems that have been described, a decision support system is planned to be built by utilizing the WP algorithm. The purpose of using the WP algorithm, to provide decision-making support in choosing alternatives as a result of information processing with a decision-making model, and to solve semi-structured and unstructured problems. Employee performance assessment will be used as a basis for evaluation to improve overall performance. Employees who are successfully selected as having the best performance will be given a reward as a form of appreciation for their achievements. The results of the employee performance assessment are the employee named MULYOKO ranked as the best performance with a score of 0.096505 and the employee with the lowest performance score REVI with a score of 0.044987.